2011
DOI: 10.1155/2011/157687
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Characterization ofGCLM-Knockout Mice, a Model for Enhanced Susceptibility to Oxidative Stress

Abstract: Glutathione (GSH) is a major player in cellular defense against oxidative stress. Deletion of the modifier subunit of glutamate cysteine ligase (GCLM), the first and the rate-limiting enzyme in the synthesis of GSH, leads to significantly lower GSH levels in all tissues including the brain. GCLM-knockout (Gclm−/−) mice may thus represent a model for compromised response to oxidative stress amenable to in vitro and in vivo investigations. In order to determine whether the diminished GSH content would by itself … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
2
19
1
Order By: Relevance
“…4 Although massively depleted of glutathione, the major antioxidant in most tissues, gclm À / À mice are seemingly healthy and normal. [3][4][5] In line with previous reports, we found that the glutathione concentration of erythrocytes from gclm À / À mice was o10% of the concentration of erythrocytes from gclm þ / þ mice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4 Although massively depleted of glutathione, the major antioxidant in most tissues, gclm À / À mice are seemingly healthy and normal. [3][4][5] In line with previous reports, we found that the glutathione concentration of erythrocytes from gclm À / À mice was o10% of the concentration of erythrocytes from gclm þ / þ mice.…”
Section: Discussionmentioning
confidence: 99%
“…4 Although massively depleted of glutathione, the major antioxidant in most tissues, gclm À / À mice are seemingly healthy and normal. [3][4][5] In line with previous reports, we found that the glutathione concentration of erythrocytes from gclm À / À mice was o10% of the concentration of erythrocytes from gclm þ / þ mice. 3,5 Glutathione is a major antioxidant of erythrocytes and reduces their considerable oxidative burden, which arises from their role as O 2 -transporting cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations